Finding of pathological thrombomodulin gene variant in a patient with idiopathic nodular glomerulosclerosis and chronic thrombotic microangiopathy-like changes. (July 2020) - Hanna, Ramy; Zuckerman, Jonathan E; Ferrey, Antoney; Torres, Everado Arias; Tonthat, Sam; Barsoum, Marina; Ghobry, Lena; Wassef, Olivia; Kalantarzadeh, Kamyar
Idiopathic nodular glomerulosclerosis is an unusual histopathological finding that has commonly been observed in male smokers with hypertension. It has remained an enigmatic condition and is best described as a diabetic pattern of glomerular injury seen in non-diabetic patients. It is also one of the few nicotine (smoking)-associated/smoking-associated patterns of renal injury. We present an even more unusual manifestation of this pathological finding in a 59-year-old Hispanic female who presented with chronic kidney disease approaching need for renal replacement therapy. The patient had idiopathic nodular glomerulosclerosis on kidney biopsy, despite no prior history of diabetes, nor smoking history, including no secondhand smoking exposure. The patient did have hypertension. The renal biopsy also showed evidence of chronic thrombotic-microangiopathic changes within arteries and arterioles. Genetic testing of the alternative pathway revealed an unusual and likely pathological variant of thrombomodulin supporting complement dysfunction as having a role in the presentation.